Convergent media and privacy - Dwyer, Tim (Palgrave global media policy and business, 2016)
"In the lightning paced digital media environment of mass-scale data collection by Google, Facebook, and security agencies like the US's National Security Agency and the UK's GCHQ, citizens should be very concerned about trends in media communications and privacy. Data retention laws are sold to us by governments on the dubious promise that by storing all of our communications metadata they will save us from those who seek to cause harm. At the same time corporations amass even more data as we merely go about our daily lives. Our privacy rights, despite recent developments like 'the right to be forgotten' found by the European Court of Justice, are diminishing, as people accept a trade-off between data disclosure and national security. Meanwhile, neoliberal ideologies about 'having nothing to hide' are exposed as at best lame, and at worst, naively complicit with the dovetailing motivations of both corporations and governments. Big data enthusiasts seem blind to both increasingly frequent data breaches and the full spectrum of hackers, and downplay their privacy consequences. Convergent Media and Privacy examines where the important human right of privacy has emerged from, where it is heading, and how new digital media corporations are reshaping its meaning in cooperation with governments. "..